Music Therapy on Pain Management Among Post-Operative Patients: A Systematic Review - Sri Utami Damayanti; Eva Herawati; Suryati Suhaemia; Natalia Suraningsih; Imansyah Abd Latif Ode; Yani Sofiani (STIKep PPNI Jawa Barat, 2022)
Aim: This review aimed to identify and analyze the existing literature related to music therapy on pain management among post-operative patients. Methods: This study utilizes a literature review approach, with research sources drawn from three databases: Proquest, Pubmed, and Google Scholar. Four suitable articles were found after screening the articles published between 2012 and 2022 in journals in English and Bahasa, with quasi-experimental research designs and True Experiments.